Photoorganocatalytic Atom Transfer Radical Addition of Bromoacetonitrile to Aliphatic Olefins - Voutyritsa, Errika; Nikitas, Nikolaos F.; Apostolopoulou, Mary K.; Gerogiannopoulou, Anna Dimitra D.; Kokotos, Christoforos G. (Synthesis, 2018)
A green and cheap protocol for the photocatalytic atom transfer radical addition (ATRA) of bromoacetonitrile to aliphatic alkenes is presented. The use of benzoin methyl ehter as the photocatalyst and irradiation using a household lightbulb leads to a highly useful synthetic method for the conversion of a wide range of substituted aliphatic olefins into the corresponding bromonitriles.
Keywords: photoorganocatalysis; photochemistry; ATRA reaction; alkenes; bromoacetonitrile; nitriles